What Are the Contextual Enablers and Impacts of Using Digital Technology to Extend Maternal and Child Health Services to Rural Areas? Findings of a Qualitative Study From Nigeria - Bassey Ebenso; Babasola Okusanya; Kehinde Okunade; David Akeju; Adegbenga Ajepe; Godwin O. Akaba; Ramsey M. Yalma; Osasuyi Dirisu; Jamilu Tukur; Manir K. Abdullahi; Okey Okuzu; Matthew J. Allsop (Frontiers Media S.A., 2021)
Background: Strengthening health systems to improve access to maternity services remains challenging for Nigeria due partly to weak and irregular in-service training and deficient data management. This paper reports the implementation of digital health tools for video training (VTR) of health workers and digitization of health data at scale, supported by satellite communications (SatCom) technology and existing 3G mobile networks.Objective: To understand whether, and under what circumstances using digital interventions to extend maternal, newborn and child health (MNCH) services to remote areas of Nigeria improved standards of healthcare delivery.Methods: From March 2017 to March 2019, VTR and data digitization interventions were delivered in 126 facilities across three states of Nigeria. Data collection combined documents review with 294 semi-structured interviews of stakeholders across four phases (baseline, midline, endline, and 12-months post-project closedown) to assess acceptability and impacts of digital interventions. Data was analyzed using a framework approach, drawing on a modified Technology Acceptance Model to identify factors that shaped technology adoption and use.Results: Analysis of documents and interview transcripts revealed that a supportive policy environment, and track record of private-public partnerships facilitated adoption of technology. The determinants of technology acceptance among health workers included ease of use, perceived usefulness, and prior familiarity with technology. Perceptions of impact suggested that at the micro (individual) level, repeated engagement with clinical videos increased staff knowledge, motivation and confidence to perform healthcare roles. At meso (organizational) level, better-trained staff felt supported and empowered to provide respectful healthcare and improved management of obstetric complications, triggering increased use of MNCH services. The macro level saw greater use of reliable and accurate data for policymaking.Conclusions: Simultaneous and sustained implementation of VTR and data digitization at scale enabled through SatCom and 3G mobile networks are feasible approaches for supporting improvements in staff confidence and motivation and reported MNCH practices. By identifying mechanisms of impact of digital interventions on micro, meso, and macro levels of the health system, the study extends the evidence base for effectiveness of digital health and theoretical underpinnings to guide further technology use for improving MNCH services in low resource settings.Trial Registration: ISRCTN32105372.